Speech in Schizophrenia - Dovetto, Francesca M. (Gruppo editoriale Tab Srl, 2024)
This volume collects six contributions by Francesca M. Dovetto focusing on peripheral language uses, i.e. those which are mostly divergent from the norm – mainly on those traditionally related to pathological language and in particular to schizophrenia – as well as a (partial) translation of the CIPPS corpus (Corpus of Spoken Pathological Schizophrenic Italian). The essays, five of which were previously published in Italian, address peripheral uses with questions regarding spoken vs written language, qualitative and quantitative analysis, and corpus linguistics.